An Analysis of Ecranisation Process of Intrinsic Elements in Novel to Film œFive Feet Apart by Rachael Lippincott - Putri, Rizki Tania; Lubis, Fauziah Khairani; Manullang, Elisa Betty (Universitas Negeri Medan, 2021)
This study aims to determine the changes experienced by intrinsic elements found in the novel